Role of Entrepreneurship Education in Development and Promotion of Entrepreneur Skills in the Youth of Madhya Pradesh - Dr. Minakshi Tripathi (International Journal of Engineering and Management Research, 2021)
Education in the area of entrepreneurship plays a significant role in the development of entrepreneurial skills in the individuals. It may help youth to develop skill, ability of decision making, risk taking ability, manage any situation, and proper acquisition of knowledge which could benefit them for starting, organizing and managing their own enterprises and became helpful in economic development. The target population is 417 graduates or post graduates students from the Entrepreneurship Development Cells (EDC) of premier institutions (two government and two private institutions) in which 136 were selected randomly as a sample for study. Descriptive and inferential statistics were used for analyzing the data with the help of SPSS 22.0 software. Present study evidences the role of EDCs in the skill development of male and female is equal in all components like ability of taking decisions, creativity, Research, Development and Innovation, taking initiatives and so on. Entrepreneur development cells of any institutions, programs and their faculties haven’t made any difference on the basic of gender. Their all programs are equal for all.